Pengaruh Brand Awareness dan Product Design terhadap Buying Decision melalui variabel Purchase Intention pada Produk AQUA Japan di Kota Serang - Bachrudin, Bachrudin; Sutisna, Sutisna; Umalihayati, Umalihayati (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the influence of brand awareness and product design on purchasing decisions through the purchase intention variable. The subjects in this research were 250 community respondents in Serang City. Data analysis tools use SPSS and SmartPLS using a Likert scale. The results of the research show that there is a significant influence between the product design variable on the purchase intention variable, but no direct influence was found between brand awareness on the purchase intention variable for AQUA Japan products in Serang City. Then there is a significant influence of the brand awareness, product design, purchase intention variables on the buying decision variable for AQUA Japan products in Serang City. This research also found that the purchase intention variable does not have a mediating effect on the influence of brand awareness on buying decisions, but the purchase intention variable can be used as a mediation on the influence of product design on buying decisions for AQUA Japan products in Serang City.